Arter att öka användningen av i Malmös urbana miljöer - Thornberg, Loui; Dahlin, Anna (2019)
The amount of impervious areas in Malmö continue to increase as the city expands. These urban areas are already difficult for trees, with their heat and drought, and they will be even more difficult with climate change. Therefore, we must use tree species that can cope with these challenges.